An Analysis of Elderly Use of Digital Technology in Thailand - Chanyawudhiwan, Gan; Mingsiritham, Kemmanat (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The elderly population is on the rise, globally. It is an age group that should live to their fullest potential to enhance the quality of their life, should be prepared to live life to the fullest in a way that benefits them, their family, and society. The elderly should be able to access digital technology and benefit from it. Therefore, it is necessary to educate the elderly choosing the right kind of digital technology to their quality of life, and protect themselves from cyber threats. This study performs an exploratory factor analysis of digital technology competency. A multistage random sampling method was used to obtain a sample of 225 elderly people in Thailand. The tool used was a questionnaire on digital technology competency, which included 45 questions on a 5-point scale. Data were analyzed using descriptive statistics and exploratory factor analysis. The exploratory factor analysis of digital technology competency for the elderly in Thailand found six important components: 1) use of mobile operating systems, 2) data file management, 3) cloud data management, 4) use of support applications, 5) use of applications for communication, and 6) use of technology for security. Thus, the elderly need to develop online media literacy to safely navigate the Internet while creatively using data found in the virtual domain